2023
DOI: 10.3389/fcvm.2023.1152568
|View full text |Cite
|
Sign up to set email alerts
|

Anderson-Fabry disease cardiomyopathy: an update on epidemiology, diagnostic approach, management and monitoring strategies

Abstract: Anderson-Fabry disease (AFD) is an X-linked lysosomal storage disorder caused by deficient activity of the enzyme alpha-galactosidase. While AFD is recognized as a progressive multi-system disorder, infiltrative cardiomyopathy causing a number of cardiovascular manifestations is recognized as an important complication of this disease. AFD affects both men and women, although the clinical presentation typically varies by sex, with men presenting at a younger age with more neurologic and renal phenotype and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 212 publications
0
1
0
Order By: Relevance
“…Indeed, the postmortem examination of Fabry hearts revealed that the greatest concentrations of glycosphingolipids were in the mitral valve ( 36 ). The most recent study revealed that in classic- FD, the prevalence of valvular disease, from moderate to severe, was 10%, with mitral and tricuspid regurgitation being the most common ( 37 , 38 ). Beyond the glycosphingolipids accumulation specifically at valvular levels, other phenomenon could be involved in FD valve dysfunction, including thickening of the sub-valvular apparatus ( 35 ) geometric distortion of the atria, valvular annulus, or aortic root dilatation ( 37 ).…”
Section: Exercise Intolerance and Fatigability In Fd Patientsmentioning
confidence: 99%
“…Indeed, the postmortem examination of Fabry hearts revealed that the greatest concentrations of glycosphingolipids were in the mitral valve ( 36 ). The most recent study revealed that in classic- FD, the prevalence of valvular disease, from moderate to severe, was 10%, with mitral and tricuspid regurgitation being the most common ( 37 , 38 ). Beyond the glycosphingolipids accumulation specifically at valvular levels, other phenomenon could be involved in FD valve dysfunction, including thickening of the sub-valvular apparatus ( 35 ) geometric distortion of the atria, valvular annulus, or aortic root dilatation ( 37 ).…”
Section: Exercise Intolerance and Fatigability In Fd Patientsmentioning
confidence: 99%